2021
DOI: 10.1371/journal.pone.0248677
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how and why audits work in improving the quality of hospital care: A systematic realist review

Abstract: Background Several types of audits have been used to promote quality improvement (QI) in hospital care. However, in-depth studies into the mechanisms responsible for the effectiveness of audits in a given context is scarce. We sought to understand the mechanisms and contextual factors that determine why audits might, or might not, lead to improved quality of hospital care. Methods A realist review was conducted to systematically search and synthesise the literature on audits. Data from individual papers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 142 publications
2
58
0
1
Order By: Relevance
“…Introducing the use of FNB needles. There is evidence to support that changes made “bottom-up” are more likely to be sustained in comparison to changes implemented “top-down” 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Introducing the use of FNB needles. There is evidence to support that changes made “bottom-up” are more likely to be sustained in comparison to changes implemented “top-down” 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Human resource audits are essential for avoiding legal and regulatory responsibility arising from an organization's human resource policies and initiatives, as well as achieving and maintaining world-class human resource practices [28]. Furthermore, one of the key goals of human resource auditing is to ensure the organization's compliance with federal rules and regulations [29]. Our finding showed that health professional hiring organizations that perform internal audits are three times more likely than those that do not have appropriate licensing practices.…”
Section: Discussionmentioning
confidence: 99%
“…Destaca-se que as organizações tem apropriado sistemas e habilidades para monitorar, rastrear e avaliar os resultados de uma auditoria (ambos antecipado e imprevisto), então as melhorias são mais prováveis de serem incorporadas e sustentadas (Hut-Mossel et al, 2021).…”
Section: Gestão Da Qualidadeunclassified